Kepercayaan Publik (Public Trust) kepada Pemerintah dalam Penanganan Kerusakan Jalan di Nagari Aie Dingin Kecamatan Lembah Gumanti Kabupaten Solok - Anggun Yulia Ningsih; Siska Sasmita (Universitas Muara Bungo, 2025)
This research is motivated by the damage to national roads in Nagari Aie Dingin, Lembah Gumanti District, Solok Regency, which has persisted for years without optimal government management. This situation has led to dissatisfaction among residents and road users, ultimately leading to a decline in public trust in the government's performance in providing basic infrastructure services. Public trust is crucial for establishing legitimacy and support for government policies, and therefore requires government attention in exercising its authority. This study aims to explain public trust in the government's handling of national road damage in Nagari Aie Dingin, Lembah Gumanti District, Solok Regency, and to identify the forms of public trust in the government within this context. This research employed a qualitative approach. Data collection techniques included in-depth interviews with residents, road users, and relevant agencies, as well as observation and documentation studies. Data analysis in this study was conducted using Kim's (2005) theory, which encompasses five indicators of public trust: credible commitment, kindness, honesty, competence, and fairness. and the forms of public trust according to Thomas (1998), namely fiduciary trust, mutual trust, and social trust. The results of the study indicate that public trust in the government in this case tends to weaken, mainly due to the quality of road repairs and the government's slow response. Nevertheless, there are still positive assessments of the government's efforts, which are beginning to show seriousness in addressing this problem. The form of trust that emerged from the public is mostly social trust, while fiduciary trust and mutual trust in the government have not yet been fully established. This study recommends the importance of consistent action and open communication between the government and the public to rebuild public trust.